A first ecological coherent assessment of eutrophication across the North-East Atlantic waters (2015–2020) - Devlin, Michelle J.; Prins, Theo C.; Enserink, Lisette; Leujak, Wera; Heyden, Birgit; Axe, Philip G.; Ruiter, Hans; Blauw, Anouk; Bresnan, Eileen; Collingridge, Kate; Devreker, David; Fernand, Liam; et al. (Frontiers in Ocean Sustainability, 2023)
This paper presents the outcomes of the fourth application of the Common Procedure for the Identification of the Eutrophication Status of the OSPAR Maritime Area conducted for the period 2015-2020 for the North East Atlantic. Previously, OSPAR has assessed eutrophication based on national assessment areas and disparate approaches lacking a transparent and comparable basis. A more harmonised approach has now been achieved through development of ecologically relevant assessment areas defined by oceanographic criteria rather than international boundaries, allowing for consistent assessments across exclusive economic zones and acknowledging that eutrophication is a transboundary problem. Thresholds that were specific for those harmonised assessment areas and eutrophication parameters have been derived primarily from an ensemble modelling approach to determine pre-eutrophic conditions. Common assessment areas and harmonised thresholds have enabled, for the first time, an objective and comparable assessment of the eutrophication status of the whole OSPAR Maritime Area. This establishes a level playing field for managing eutrophication and a solid basis for deriving OSPAR nutrient reduction targets as a prerequisite for targeted and successful regional eutrophication management. This assessment shows that eutrophication problem areas persist along the continental coasts from France to Denmark/Sweden and in the Greater North Sea and the Bay of Biscay and Iberian coast. The main areas affected by eutrophication are the plumes and adjacent coastal areas in the Greater North Sea and Bay of Biscay/Iberian Coast, with riverine nutrient inputs remaining the major source of nutrient pollution. Approximately 6% (152 904 km2) of the OSPAR Maritime Area is eutrophic, with the impacted area supporting many important ecosystem services. 58% of river plume areas, 22% of the coastal areas and 10% of the shelf areas were classified as problem areas. Application of the current assessment process to historical data from the previous three OSPAR assessment periods shows a gradual improvement since 2000. However, the OSPAR 2010 objective “to combat eutrophication, with the ultimate aim of achieving and maintaining a healthy marine environment where anthropogenic eutrophication does not occur” has not yet been fully achieved. Further measures to reduce nutrient loads are needed to ensure long-term sustainability of our coastal waters.